A new clionaid sponge infests live corals on the west coast of India (Porifera, Demospongiae, Clionaida). Issue 2 (17th February 2019) - Mote, Sambhaji; Schönberg, Christine H. L.; Samaai, Toufiek; Gupta, Vishal; Ingole, Baban
Abstract : Coral reef ecosystems depend on the balanced interplay of constructive and destructive processes and are increasingly threatened by environmental change. In this context bioeroding sponges play a significant role in carbonate cycling and sediment production. They occasionally aggravate erosional processes on disturbed reefs. Like other coral ecosystems, Indian reefs have suffered from local and global effects. However, the systematic affiliation and diversity of many Indian bioeroding sponges and their infestation rates are largely confused or unknown. The present study describes a new bioeroding sponge species, Cliona thomasi sp. nov. from the central west coast of India. It belongs to the Cliona viridis species complex, displaying the key characters of tylostyles and spirasters, as well as harbouring photosymbiotic dinoflagellates. Specific morphological characteristics and molecular data from nrITS1 DNA and 28S rDNA distinguished C. thomasi sp. nov. from other known C. viridis complex and a number of Spheciospongia species. The historic sample of ' Suberites coronarius ' from Mergui Archipelago ( sensu Carter, 1887 ), but not from the Caribbean ( sensu Carter, 1882 ), is conspecific with C. thomasi sp. nov. Cliona thomasi sp. nov. is locally very abundant, appears to be a key bioeroder, and thus regular monitoring of its abundance, distribution and infestation patterns is recommended.